Optical diagnostic system for visualization subcutaneous blood vessels - Opilski, Z.; Pustelny, T.; Pach, M.; Hejczyk, T. (Opto-Electronics Review, 2020)
The paper presents a research concerning the issue of visualization of blood vessels in the human body. In the initial phase of the investigations the focus was on understanding the optical properties of human body tissues. Optical transmittance of human skin was measured. Skin transmittance reaches the maximum at around 670–850 nm and 970–1100 nm. The optimal wavelength suitable for work in reflected and transmitted light was chosen. It was based on extracting blood vessels from the image for using them further in a developed system. A unique measuring system with an integrated illuminator and highly sensitive light detectors for medical imaging and stereoscopic observation was created. The high usable value of the developed system was largely gained by the original numerical program for development of measurement results. The elaborated system of blood vessels’ visualization is a mobile device. It was tested for imaging subcutaneous blood vessels. Three-dimensional observation of circulation and microcirculation in subcutaneous breast tissues is possible. Practical tests of the elaborated device for blood vessels’ medical stereoscopic observations were presented. Tests at a wavelength of 850 nm were performed. It is planned to conduct patient tests in the future at the Maria Skłodowska-Curie Institute - Oncology Center (MSCI), the Branch in Gliwice, Poland.